2014
DOI: 10.1186/1742-2094-11-38
|View full text |Cite
|
Sign up to set email alerts
|

NFκB-mediated CXCL1 production in spinal cord astrocytes contributes to the maintenance of bone cancer pain in mice

Abstract: BackgroundBone cancer pain (BCP) is one of the most disabling factors in patients suffering from primary bone cancer or bone metastases. Recent studies show several chemokines (for example, CCL2, CXCL10) in the spinal cord are involved in the pathogenesis of BCP. Here we investigated whether and how spinal CXCL1 contributes to BCP.MethodsMouse prostate tumor cell line, RM-1 cells were intramedullary injected into the femur to induce BCP. The mRNA expression of CXCL1 and CXCR2 was detected by quantitative real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 57 publications
7
59
0
Order By: Relevance
“…We demonstrated that NF-κB was specifically co-localized with astrocytes in the spinal cord of BCP rats, which is consistent with previous literature. For example, Xu et al [8] reported that NF-κB contributed to BCP via the mediation of CXCL1 production in spinal astrocytes; these authors also highlighted that an intrathecally injected inhibitor of NF-κB significantly attenuated nociceptive behavior. Similarly, other studies based on neuropathic pain have demonstrated that targeted blockades of NF-κB in the spinal cord alleviated pain perception [13,15] .…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that NF-κB was specifically co-localized with astrocytes in the spinal cord of BCP rats, which is consistent with previous literature. For example, Xu et al [8] reported that NF-κB contributed to BCP via the mediation of CXCL1 production in spinal astrocytes; these authors also highlighted that an intrathecally injected inhibitor of NF-κB significantly attenuated nociceptive behavior. Similarly, other studies based on neuropathic pain have demonstrated that targeted blockades of NF-κB in the spinal cord alleviated pain perception [13,15] .…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…Over the previous few decades, BCP models have been successfully established [5] , and there is increasing evidence that indicates spinal astrocytes participate in the process [6,7] by releasing pro-inflammatory cytokines and chemokines [7][8][9] . Moreover, nuclear factor kappa B (NF-κB), an important transcriptional factor mediating cytokine production [8,10,11] , is activated in spinal astrocytes during a chronic pain state [8,12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suramin or A317491 was intrathecally (it) injected once. Intrathecal injection was made with a 27 G needle between the L5 and L6 intervertebral space to deliver the reagents to the cerebral spinal fluid as described previously (21,45). Buto, Phen, or Prop was intraperitoneally injected once daily for 7 consecutive days for molecular expression experiments and once for behavioral test.…”
Section: Methodsmentioning
confidence: 99%
“…(6) The latest study also showed that NFκB mediated the release of CXCL1 from spinal astrocytes, which could act on CXCR2 on neurons in BCP mice. It suggested that CXCL1/CXCR2-mediated astroglia-neuron interaction plays a significant role in the maintenance of tumoral hypersensitivity (Xu et al, 2014). In conclusion, understanding the mechanisms of pro-inflammatory mediators in the context of BCP models is an ongoing effort that requires research attention.…”
Section: Mechanisms Of Bcpmentioning
confidence: 99%